Plasticity of Fear and Safety Neurons of the Amygdala in Response to Fear Extinction - Sangha, Susan (Frontiers in Behavioral Neuroscience, 2015)
Fear inhibition learning induces plasticity and remodeling of circuits within the amygdala. Most studies examine these changes in nondiscriminative fear conditioning paradigms. Using a discriminative fear, safety and reward conditioning task, Sangha et al (2013) have previously reported several neural microcircuits within the basal amygdala which discriminate among these cues, including a subpopulation of neurons responding selectively to a safety cue and not a fear cue. Here, the hypothesis that these ‘safety’ neurons isolated during discriminative conditioning are biased to become fear cue responsive as a result of extinction, when fear behavior diminishes, was tested. Although 41% of ‘safety’ neurons became fear cue responsive as a result of extinction, the data revealed that there was no bias for these neurons to become preferentially responsive during fear extinction compared to the other identified subgroups. In addition to the plasticity seen in the ‘safety’ neurons, 44% of neurons unresponsive to either the fear cue or safety cue during discriminative conditioning became fear cue responsive during extinction. Together these emergent responses to the fear cue as a result of extinction support the hypothesis that new learning underlies extinction. In contrast, 47% of neurons responsive to the fear cue during discriminative conditioning became unresponsive to the fear cue during extinction. These findings are consistent with a suppression of neural responding mediated by inhibitory learning, or, potentially, by direct unlearning. Together, the data support extinction as an active process involving both gains and losses of responses to the fear cue and suggests the final output of the integrated basal amygdala circuit in influencing fear behavior is a balance of excitation and inhibition, and perhaps reversal of learning-induced changes.